Development of Numeracy Problems with the Context of Bee Cultivation Activity for Junior High School Students - Erni Maidiyah; Rahmadia Tiara Agusta; Rahmah Johar; Mimie Saputri; Dewi Andayani (Universitas Syiah Kuala, 2023)
The minimum competency assessment evaluates the numeracy skills of Indonesian students, aiming to facilitate the development of personal skills for self-improvement and contribute positively to society. The low numeracy skills among students are the lack of familiarity and infrequent practice in solving numeracy problems. This study aimed to determine the characteristics of numeracy problems with a context of biodiversity conservation using the Research and Development (RD) method by Tessmer. This model includes preliminary, self-evaluation, expert review, one-to-one, small group, and field tests. The subjects of this study were Year 7 students from one junior high school in Banda Aceh, Indonesia. This study developed were 20 problems. The validity data result of the questions is 0.88 with valid criteria, and the practicality data result of the questions is 89.7% with highly practical criteria. Furthermore, the potential effect is obtained from the average student score (75.39), indicating good criteria. It can be stated that numeracy questions with a context of bee cultivation activity met the valid and practical criteria, and have a potential effect. Therefore, teachers can use these questions as instruments to improve students' numeracy skills.